Metal-CNTs-TiO2 composite material and preparation method thereof
By depositing TiO2 inside the carbon nanotube and depositing precious metal metal-CNTs-TiO2 composite materials on the surface, the problems of insufficient light and low visible light utilization are solved, the catalytic efficiency is significantly improved, and it is suitable for the decomposition of harmful substances in the air.
Patent Information
- Application Number
- CN202411262088.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-10
AI Technical Summary
The existing photocatalysts are not effective in environments with insufficient lighting and have low utilization of visible light, which limits their application range.
Using metal-CNTs-TiO2 composite materials, catalytic efficiency is improved by depositing TiO2 inside carbon nanotubes and depositing precious metals on the surface, and the preparation process is simplified by hydrothermal reaction and precious metal deposition steps.
The absorption rate and light response range of TiO2 to visible light are improved, the electron transmission speed is enhanced, the catalytic efficiency is significantly improved, and it is suitable for photocatalytic reactions.
Smart Images

Figure CN119140089A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of air purification materials, and in particular to a metal-CNTs-TiO2 composite material and a preparation method thereof. Background Art
[0002] With the development of civilization, major problems such as environmental pollution and ecological destruction have emerged, threatening the future survival and development of all mankind. Environmental pollution is one of the most concerned issues of mankind in this century. With the increasing awareness of indoor environmental protection, people are eager to have a safe, comfortable and healthy living space. However, a considerable number of homes and office buildings are in serious indoor pollution due to disorderly decoration or neglect of environmental sanitation management during construction.
[0003] In the field of air purification, the current popular method is to use photocatalysts for decomposition. Photocatalysts (titanium dioxide) absorb light energy under specific lighting conditions to generate electron-hole pairs, which react with OH-, H2O, O2, etc. adsorbed on their surfaces to generate free radicals. These free radicals can react with organic matter adsorbed on their surfaces to degrade the organic matter into environmentally friendly water and carbon dioxide. Therefore, photocatalytic technology can be used to degrade organic pollutants in the air. However, existing photocatalyst products have the following disadvantages:
[0004] ① Light source and lighting requirements: Photocatalysts require sufficient natural light or artificial light to work, which means that in an indoor environment with insufficient light, photocatalysts may not work optimally.
[0005] ② Technical limitations: TiO2 photocatalysts have a low utilization rate of visible light and usually need to be used in conjunction with ultraviolet light, which limits the application of photocatalysts in environments without ultraviolet light sources. Summary of the invention
[0006] The present invention provides a metal-CNTs-TiO2 composite material, which has a special structure, wherein TiO2 is deposited inside carbon nanotubes and noble metals are deposited on the surface of carbon nanotubes. The structure has the advantages of high catalytic efficiency when catalytically decomposing harmful substances such as formaldehyde in the air. The present invention also provides a method for preparing the metal-CNTs-TiO2 composite material, which can obtain the metal-CNTs-TiO2 composite material of the present invention, and the method is simple and easy to industrialize.
[0007] On the one hand, the present invention provides a metal-CNTs-TiO2 composite material, which is composed of carbon nanotubes, TiO2 and precious metals, and is characterized in that TiO2 is deposited inside the carbon nanotubes and the precious metals are deposited on the surface of the carbon nanotubes.
[0008] In some embodiments, the carbon nanotubes have an outer diameter of 20-80 nm.
[0009] In some embodiments, the outer diameter of the carbon nanotubes is 20-40 nm or 30-80 nm.
[0010] In some embodiments, the noble metal is selected from Au, Ag, Pt, Pd, Rh, or Ir.
[0011] In some embodiments, the noble metal is selected from Au.
[0012] In some embodiments, TiO2 is crystalline with a particle size of 10-30 nm.
[0013] In some embodiments, the mass ratio of precious metal, CNTs, and TiO2 is (1-2):1:(5-8).
[0014] On the other hand, the present invention provides a method for preparing a metal-CNTs-TiO2 composite material, characterized by comprising:
[0015] 1) Preparation of CNTs-TiO2, including:
[0016] 1.1) Preparation of TiO2 precursor solution: dissolving a titanium source in a first solvent to obtain a solution, wherein the molar ratio of the titanium source to the first solvent is 1:(3-20);
[0017] 1.2) Hydrothermal reaction: CNTs powder is mixed with TiO2 precursor solution, the mass ratio of CNTs powder to TiO2 precursor solution is 1:(25-50), and the reaction is carried out in a closed state at a temperature of 120-200°C and a pressure of 2-5atm for 1-5 hours to obtain CNTs-TiO2.
[0018] 2) Precious metal deposition: Mix the precious metal salt solution with CNTs-TiO2, add a reducing agent to deposit the metal on the surface of CNTs-TiO2, and obtain a metal-CNTs-TiO2 composite material.
[0019] The first solvent is added to the titanium source to dissolve the titanium source. In order to better deposit it in the carbon nanotubes, the first solvent can be a solvent that can dissolve the titanium source. The first solvent is selected based on the selection of the titanium source itself and the properties of the carbon nanotubes. Specifically, it can be a hydrophilic solvent, preferably alcohol or water, or a mixed solution thereof, such as methanol, ethanol, water, a mixture of methanol and water, or a mixture of ethanol and water.
[0020] In some embodiments, the preparation of the CNTs-TiO2 further includes pretreatment of carbon nanotubes CNTs, wherein the carbon nanotubes CNTs are dispersed with a second solution and then dried to obtain carbon nanotubes CNTs powder.
[0021] In some embodiments, the purpose of pretreatment of carbon nanotubes (CNTs) is to enable the carbon nanotubes to be better dispersed to facilitate subsequent reactions. Therefore, a solvent is used, preferably a solvent that can disperse the carbon nanotubes, such as a hydrophilic solvent, preferably alcohol or water, or a mixed solution thereof, such as methanol, ethanol, water, a mixture of methanol and water, or a mixture of ethanol and water.
[0022] The first solvent is mainly used to dissolve and disperse the titanium source so that it can be deposited in the CNTs later. Generally, the molar ratio of the titanium source to the first solvent is 1: (3-20), and specifically 1:5, 1:10, 1:15 or 1:20 can be used.
[0023] The mass ratio of CNTs powder to TiO2 precursor solution is 1:(5-10), and specifically can be 1:5, 1:6:1:7, 1:8, 1:9 or 1:10.
[0024] In some embodiments, the preparation of the CNTs-TiO2 further includes subjecting the CNTs-TiO2 to a heat treatment in an inert gas after the hydrothermal reaction, wherein the heat treatment temperature is 800 to 1000° C. and the heat treatment time is 20 to 60 minutes.
[0025] The inert gas can be nitrogen, helium or other conventional gases that have no effect on the reaction.
[0026] In some embodiments, during the preparation of the CNTs-TiO2, the pH of the TiO2 precursor solution is adjusted to 1-3.
[0027] The pH can be adjusted using conventional pH adjusters such as sulfuric acid and acetic acid that do not affect the reaction.
[0028] In the preferred embodiment, the nucleation and growth of TiO2 can be controlled by adjusting the pH.
[0029] In some embodiments, the titanium source is selected from one or more of tetrabutyl titanate (Ti(OC4H9)4), tetraisopropyl titanate (Ti(OiPr)4), isopropyl titanate, isopropoxide titanium, and titanium tetrachloride.
[0030] In some embodiments, the noble metal salt is selected from: chloroaurate.
[0031] In some embodiments, the reducing agent is selected from the group consisting of sodium citrate, sodium borohydride, ascorbic acid, sodium bisulfite, hydrazine hydrate, or a combination thereof.
[0032] The dosage of the reducing agent of the present invention is related to the type of the noble metal salt, the amount added and the type of the reducing agent itself. There is no special requirement for the selection of dosage, and the conventional dosage in the art can be used.
[0033] In some embodiments, the first solution or the second solvent is selected from: an alcohol solvent (eg, methanol, ethanol or isopropanol), water, or a mixture thereof.
[0034] Preferably, ultrapure water is used.
[0035] Beneficial Effects
[0036] (1) Carbon nanotube doping can increase the absorption rate of TiO2 to visible light, expand the light response range, accelerate electron transfer, reduce carrier recombination, and improve catalytic efficiency. The in-situ synthesis of nano-titanium dioxide is used to control the nucleation of nano-titanium dioxide inside the carbon nanotube and its outward growth, forming a short rod structure with carbon nanotubes as the matrix and titanium dioxide as the epitaxial structure. This structure can reflect the incident light multiple times, thereby increasing the absorption range of light wavelengths and improving photocatalytic efficiency.
[0037] (2) Surface deposition of gold particles reduces the bandgap of TiO2, increases its response wavelength, and improves the utilization rate of light. A joint structure of TiO2 and precious metals is formed on the surface of TiO2, which effectively reduces the combination rate of holes and electrons and significantly enhances the catalytic efficiency of nano-TiO2 in photocatalytic reactions.
[0038] (3) Control the crystallinity and grain size of the material to reduce the recombination centers inside the catalytic material. When the grain size is smaller than the diffusion length of electrons or holes, the number of carriers increases and the number of recombination centers decreases, which greatly improves the migration efficiency of the material and thus improves the photocatalytic efficiency.
[0039] Terminology
[0040] Certain embodiments of the present invention are now described in detail. The present invention is intended to cover all substitutions, modifications and equivalent technical solutions, which are all included in the scope of the present invention as defined in the claims. It should be appreciated by those skilled in the art that many methods and materials similar or equivalent to those described herein can be used to practice the present invention. The present invention is by no means limited to the methods and materials described herein. In the event that one or more of the combined documents, patents and similar materials are different from or contradictory to the present application (including but not limited to defined terms, term applications, described technologies, etc.), the present application shall prevail.
[0041] It should be further appreciated that certain features of the invention, which for clarity are described in multiple separate embodiments, may also be provided in combination in a single embodiment. Conversely, various features of the invention, which for brevity are described in a single embodiment, may also be provided separately or in any suitable sub-combination.
[0042] Unless otherwise specified, all technical terms used in the present invention have the same meaning as commonly understood by those skilled in the art to which the present invention belongs. All patents and publications related to the present invention are incorporated herein by reference in their entirety.
[0043] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0044] In the following, all numbers disclosed herein are approximate, regardless of whether the words "about" or "approximately" are used. The value of each number may vary by 1%, 2%, 5%, 7%, 8%, 10%, 15% or 20%. Whenever a number having a value of N is disclosed, any number having a value of N+ / -1%, N+ / -2%, N+ / -3%, N+ / -5%, N+ / -7%, N+ / -8%, N+ / -10%, N+ / -15% or N+ / -20% is explicitly disclosed, where "+ / -" means plus or minus. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a structural diagram of the photocatalyst prepared in Example 1.
[0046] Figure 2 This is a structural diagram of the photocatalyst prepared in Example 2.
[0047] Figure 3 This is a structural diagram of the photocatalyst prepared in Example 3.
[0048] Figure 4 This is a structural diagram of the photocatalyst prepared in Comparative Example 1.
[0049] Figure 5 An example of a hazardous gas decomposition test device system. DETAILED DESCRIPTION
[0050] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concepts of the present disclosure. Such structures and technologies are also described in many publications.
[0051] The reagents used in the present invention can be purchased from the market or prepared by the method described in the present invention.
[0052] Example 1
[0053] S1: CNTs-TiO2 preparation:
[0054] (1) Add carbon nanotubes (CNTs) (outer diameter 20-40 nm) and ultrapure water and ethanol mixed solution into the reactor, disperse them by ultrasonic, filter them by vacuum filtration, and then put them in a drying oven at 80-100°C for drying before use. The mass fraction ratio of CNTs to the mixed solution is 1:50; the mass fraction ratio of water to ethanol is 3:7.
[0055] (2) TiO2 precursor solution: Use the titanium organic compound tetrabutyl titanate (Ti(OC4H9)4) as the titanium source and dissolve it in an appropriate ethanol solvent. The molar ratio of the titanium source to ethanol is 1: (3-20), and in this embodiment it is 1:10.
[0056] (3) Adjusting the pH value of the TiO2 precursor solution: Adding acetic acid to adjust the solution pH to ≈ 2 facilitates the control of the nucleation and growth of TiO2.
[0057] (4) Hydrothermal reaction: (1) CNTs powder and (3) adjusted TiO2 precursor solution are placed in an autoclave, set the temperature to 160°C and the pressure to 3 atm (atmospheric pressure), and the reaction is carried out in a closed environment. The reaction time is about 2 hours. The mass ratio of (1) CNTs powder to (3) adjusted TiO2 precursor solution is 1:35.
[0058] (5) Cooling and separation: After the reaction is completed, the autoclave is cooled to room temperature, and then the autoclave is opened and filtered to obtain the carbon nanotube product with deposited titanium dioxide.
[0059] (6) Washing, drying, and calcining: The product was washed with an ethanol solvent to remove residual reactants and by-products, and then filtered, dried, and heat treated at 900°C for 30 min in a nitrogen atmosphere to improve the crystallinity of CNTs-TiO2. Dry CNTs-TiO2 nanopowder A was obtained.
[0060] S2: Preparation of Au-CNTs-TiO2:
[0061] Add solvent, water is used as solvent in this case, and add 1g CNTs-TiO2 nanopowder A prepared in S1 above and fully disperse it; add 15g diluted 2% chloroaurate solution and stir evenly; finally add 0.2g sodium citrate and 0.3g sodium borate, stir at room temperature, wait for gold particles to be deposited on the surface of CNTs-TiO2 nanopowder, filter, filter and dry to obtain Au-CNTs-TiO2 photocatalyst A. The structure is as follows Figure 1 , TiO2 is deposited inside the carbon nanotubes, and Au is deposited outside the carbon nanotubes.
[0062] Example 2
[0063] S1: CNTs-TiO2 preparation:
[0064] (1) Add carbon nanotubes (CNTs) (outer diameter 30-80 nm) and ultrapure water and ethanol mixed solution into a reactor, perform ultrasonic dispersion, and place in a drying oven at 80-100°C for drying before use. The mass fraction ratio of CNTs to the mixed solution is 1:50; the mass fraction ratio of water to ethanol is 3:7.
[0065] (2) TiO2 precursor solution: Use the titanium organic compound tetrabutyl titanate (Ti(OC4H9)4) as the titanium source and dissolve it in an appropriate ethanol solvent. The molar ratio of the titanium source to ethanol is 1: (3-20), and in this embodiment it is 1:10.
[0066] (3) Adjusting the pH value of the TiO2 precursor solution: Adding acetic acid to adjust the solution pH to ≈ 2 facilitates the control of the nucleation and growth of TiO2.
[0067] (4) Hydrothermal reaction: (1) CNTs powder and (3) adjusted TiO2 precursor solution are placed in an autoclave, set the temperature to 160°C and the pressure to 3 atm (atmospheric pressure), and the reaction is carried out in a closed environment. The reaction time is about 2 hours. The mass ratio of (1) CNTs powder to (3) adjusted TiO2 precursor solution is 1:35.
[0068] (5) Cooling and separation: After the reaction is completed, the autoclave is cooled to room temperature, and then the autoclave is opened and filtered to obtain the carbon nanotube product with deposited titanium dioxide.
[0069] (6) Washing, drying, and calcining: The product was washed with an ethanol solvent to remove residual reactants and by-products, and then filtered, dried, and heat treated at 900°C for 30 min in a nitrogen atmosphere to improve the crystallinity of CNTs-TiO2. Dry CNTs-TiO2 nanopowder B was obtained.
[0070] S2: Preparation of Au-CNTs-TiO2:
[0071] Add water to the reactor, add 1g of CNTs-TiO2 nanopowder B prepared in S1 and fully disperse; add 15g of 2% diluted chloroaurate solution and stir evenly; finally add 0.2g of sodium citrate and 0.3g of sodium borate, stir at room temperature, wait for gold particles to be deposited on the surface of CNTs-TiO2 nanopowder, filter and dry to obtain Au-CNTs-TiO2 photocatalyst B. The structure is as follows Figure 2 , TiO2 is deposited inside the carbon nanotubes, and Au is deposited outside the carbon nanotubes.
[0072] Example 3
[0073] S1: CNTs-TiO2 preparation:
[0074] (1) Add carbon nanotubes (CNTs) (outer diameter 20-40 nm) and ultrapure water and ethanol mixed solution into a reactor, perform ultrasonic dispersion, and place in a drying oven at 80-100°C for drying before use. The mass fraction ratio of CNTs to the mixed solution is 1:50; the mass fraction ratio of water to ethanol is 3:7.
[0075] (2) TiO2 precursor solution: Use the titanium organic compound tetrabutyl titanate (Ti(OC4H9)4) as the titanium source and dissolve it in an appropriate ethanol solvent. The molar ratio of the titanium source to ethanol is 1: (3-20), and in this embodiment it is 1:10.
[0076] (3) Adjusting the pH value of the TiO2 precursor solution: Adding acetic acid to adjust the solution pH to ≈ 2 facilitates the control of the nucleation and growth of TiO2.
[0077] (4) Hydrothermal reaction: (1) CNTs powder and (3) adjusted TiO2 precursor solution are placed in an autoclave, set the temperature to 160°C and the pressure to 3 atm (atmospheric pressure), and the reaction is carried out in a closed environment. The reaction time is about 1 hour. The mass ratio of (1) CNTs powder to (3) adjusted TiO2 precursor solution is 1:35.
[0078] (5) Cooling and separation: After the reaction is completed, the autoclave is cooled to room temperature, and then the autoclave is opened and filtered to obtain the carbon nanotube product with deposited titanium dioxide.
[0079] (6) Washing, drying, and calcining: The product was washed with an ethanol solvent to remove residual reactants and by-products, and then filtered, dried, and heat treated at 900°C for 30 min in a nitrogen atmosphere to improve the crystallinity of CNTs-TiO2. Dry CNTs-TiO2 nanopowder C was obtained.
[0080] S2: Preparation of Au-CNTs-TiO2:
[0081] Add water to the reactor, add 1g of CNTs-TiO2 nanopowder C prepared in S1 and fully disperse; add 15g of 2% diluted chloroaurate solution and stir evenly; finally add 0.2g of sodium citrate and 0.3g of sodium borate, stir at room temperature, wait for gold particles to be deposited on the surface of CNTs-TiO2 nanopowder, filter and dry to obtain Au-CNTs-TiO2 photocatalyst C. The structure is as follows Figure 3 , TiO2 is deposited inside the carbon nanotubes, and Au is deposited outside the carbon nanotubes.
[0082] Example 4
[0083] S1: CNTs-TiO2 preparation:
[0084] According to Example 1, dry CNTs-TiO2 nanopowder A was obtained.
[0085] S2: Preparation of Pt-CNTs-TiO2:
[0086] Add water to the reactor, add 1g of CNTs-TiO2 nanopowder A prepared in S1 and fully disperse; add 15g of diluted chloroplatinic acid and stir evenly; finally add 0.2g of sodium citrate and 0.3g of sodium borate, stir at room temperature, wait for gold particles to be deposited on the surface of CNTs-TiO2 nanopowder, filter, filter and dry to obtain platinum-CNTs-TiO2 photocatalyst A1. Through electron microscopy, platinum-CNTs-TiO2 photocatalyst A1 has the same structure as Au-CNTs-TiO2 photocatalyst A.
[0087] Example 5
[0088] S1: CNTs-TiO2 preparation:
[0089] (1) TiO2 precursor solution: Use the titanium organic compound tetrabutyl titanate (Ti(OC4H9)4) as the titanium source and dissolve it in an appropriate ethanol solvent. The molar ratio of the titanium source to ethanol is 1: (3-20), and in this embodiment it is 1:10.
[0090] (2) Hydrothermal reaction: CNTs powder and the adjusted TiO2 precursor solution are placed in an autoclave, and the temperature is set to 160°C and the pressure is 3 atm (atmospheric pressure). The reaction is carried out in a closed environment. The reaction time is about 2 hours. The mass ratio of (1) CNTs powder to (3) the adjusted TiO2 precursor solution is 1:35.
[0091] (3) Cooling and separation: After the reaction is completed, the autoclave is cooled to room temperature, and then the autoclave is opened and filtered to obtain the deposited titanium dioxide nanotube product. Through electron microscopy, TiO2 is deposited inside the carbon nanotubes.
[0092] S2: Preparation of Au-CNTs-TiO2:
[0093] Au-CNTs-TiO2 photocatalyst A2 was obtained by preparing S2Au-CNTs-TiO2 according to Example 1. Through electron microscopy, Au-CNTs-TiO2 photocatalyst A2 also has TiO2 deposited inside the carbon nanotubes and noble metals deposited on the surface of the carbon nanotubes.
[0094] Comparative Example 1
[0095] S1: CNTs-TiO2 preparation:
[0096] (1) TiO2 precursor solution: Use the titanium organic compound tetrabutyl titanate (Ti(OC4H9)4) as the titanium source and dissolve it in an appropriate ethanol solvent. The molar ratio of the titanium source to ethanol is 1: (3-20), and the comparative example is 1:10.
[0097] (2) Adjusting the pH value of the TiO2 precursor solution: Adding acetic acid to adjust the solution pH to ≈ 2 facilitates the control of the nucleation and growth of TiO2.
[0098] (3) Hydrothermal reaction: The TiO2 precursor solution adjusted in (2) is placed in an autoclave, the temperature is set to 160°C and the pressure is 3 atm (atmospheric pressure), and the reaction is carried out in a closed environment. The reaction time is about 2 hours.
[0099] (4) Add carbon nanotubes (CNTs) (outer diameter 20-40 nm) and ultrapure water and ethanol mixed solution into the reactor, perform ultrasonic dispersion, and place in a drying oven at 80-100° C. for drying before use. The mass fraction ratio of CNTs to the mixed solution is 1:50; the mass fraction ratio of water to ethanol is 3:7.
[0100] (5) Add the dried CNTs powder of (4) to the solution of (3), wherein the mass ratio of the CNTs powder to the adjusted TiO2 precursor solution of (2) is 1:35.
[0101] (6) Cooling and separation: After the reaction is completed, the autoclave is cooled to room temperature, and then the autoclave is opened to take out the product.
[0102] (7) Washing, drying, and calcining: The product was washed with an ethanol solvent to remove residual reactants and by-products, and then filtered, dried, and heat treated at 900°C for 30 min in a nitrogen atmosphere to improve the crystallinity of CNTs-TiO2. Dry CNTs-TiO2 nanopowder D was obtained.
[0103] S2: Preparation of Au-CNTs-TiO2:
[0104] Add water to the reactor, add 1g CNTs-TiO2 nanopowder D and fully disperse; add 15g diluted 2% chloroaurate solution and stir evenly; finally add 0.2g sodium citrate and 0.3g sodium borate, stir at room temperature, wait for gold particles to deposit on the surface of CNTs-TiO2 nanopowder, and dry to obtain Au-CNTs-TiO2 photocatalyst D. The structure is as follows Figure 4 , TiO2 and Au deposition are both outside the carbon nanotubes.
[0105] Test and inspection of photocatalyst decomposition effect
[0106] Test system:
[0107] You can use Figure 5 Test device system. Test device system reliability test: at 1m 3 1 ul of toluene, the source of pollution, was placed in a light-proof container. The circulating fan was turned on for 10 minutes to ensure that the toluene was completely evaporated. The concentration was tested using a detection device and the measured concentrations were 10.2 mg / m 3 , 10mg / m 3 , 10.10mg / m 3 , proving the reliability of medicines and containers.
[0108] Test method:
[0109] In 1m 3 Place 1ul of formaldehyde, a pollution source, and different samples in a light-proof container. Use lamps (which can be ultraviolet lamps or lamps of different color temperatures) as light sources. Figure 5 The test device system was turned on for 10 minutes to ensure that the formaldehyde was completely volatilized. The PPM-400ST high-precision formaldehyde analyzer was used to test the concentration and record the data. The test results of the ultraviolet lamp as the light source are shown in Table 1, and the test results of the fluorescent lamp as the light source are shown in Table 2.
[0110] Table 1: Formaldehyde decomposition test (UV lamp as light source)
[0111]
[0112] Table 2: Formaldehyde decomposition test (fluorescent lamp as light source)
[0113]
[0114] In summary, the use of the photocatalyst having the structure described in the present invention for air purification has a faster decomposition efficiency and more thorough decomposition of formaldehyde, a harmful substance.
[0115] The method of the present invention has been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein within the content, spirit and scope of the present invention to implement and apply the technology of the present invention. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters. It is particularly important to point out that all similar replacements and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention.
Claims
1. A metal-CNTs-TiO2 composite material, the metal-CNTs-TiO2 composite material is composed of carbon nanotubes, TiO2 and precious metals, characterized in that: TiO2 is deposited inside the carbon nanotubes, and the noble metals are deposited on the surface of the carbon nanotubes.
2. The metal-CNTs-TiO2 composite material according to claim 1, characterized in that: The outer diameter of carbon nanotubes is 20-80nm.
3. The metal-CNTs-TiO2 composite material according to claim 1, characterized in that: The noble metal is selected from Au, Ag, Pt, Pd, Rh or Ir.
4. The metal-CNTs-TiO2 composite material according to claim 1, characterized in that: TiO2 is crystalline and its particle size is 10-30nm.
5. The metal-CNTs-TiO2 composite material according to any one of claims 1 to 4, characterized in that: The mass ratio of precious metals, CNTs, and TiO2: (1-2): 1: (5-8).
6. A method for preparing a metal-CNTs-TiO2 composite material, characterized in that: include: 1) Preparation of CNTs-TiO2, including: 1.1) Preparation of TiO2 precursor solution: dissolving a titanium source in a first solvent to obtain a solution, wherein the molar ratio of the titanium source to the first solvent is 1:(3-20); 1.2) Hydrothermal reaction: CNTs powder is mixed with TiO2 precursor solution, the mass ratio of CNTs powder to TiO2 precursor solution is 1:(25-50), and the reaction is carried out in a closed state at a temperature of 120-200°C and a pressure of 2-5atm for 1-5 hours to obtain CNTs-TiO2. 2) Precious metal deposition: Mix the precious metal salt solution with CNTs-TiO2, add a reducing agent to deposit the metal on the surface of CNTs-TiO2, and obtain a metal-CNTs-TiO2 composite material.
7. The preparation method according to claim 6, characterized in that: The preparation of CNTs-TiO2 also includes pretreatment of carbon nanotubes CNTs, dispersing the carbon nanotubes CNTs with a second solution, and then drying to obtain carbon nanotubes CNTs powder.
8. The preparation method according to claim 6, characterized in that: In the preparation of the CNTs-TiO2, after the hydrothermal reaction, the CNTs-TiO2 is further subjected to heat treatment in an inert gas, the heat treatment temperature being 800-1000°C and the heat treatment time being 20-60 minutes.
9. The preparation method according to claim 6, characterized in that: During the preparation of the CNTs-TiO2, the pH of the TiO2 precursor solution is adjusted to 1-3.
10. The preparation method according to any one of claims 1 to 9, characterized in that: The titanium source is selected from one or more of tetrabutyl titanate, tetraisopropyl titanate, isopropyl titanate, isopropoxy titanium, and titanium tetrachloride; The noble metal salt is selected from: chloroaurate; and / or The reducing agent is selected from: sodium citrate, sodium borohydride, ascorbic acid, sodium bisulfite, hydrazine hydrate or a combination thereof; and / or The first solution or the second solvent is selected from: an alcohol solvent (eg, methanol, ethanol or isopropanol), water or a mixture thereof.
Citation Information
Patent Citations
Preparation method of nano-gold-modified TiO2 / carbon nano-tube composite photocatalyst
CN108579737A
Purification of VOCs under photoinduced heat-driven catalysis of Pt-CNTs
CN108654601A
Carbon-coated noble metal monatomic supported catalyst as well as preparation method and application thereof
CN117482938A
Hybrid drive module using fluid clutch and operating method tehreof
KR102335206B1
Hybrid catalyst, method of fabricating the same, and fuel cell comprising the same
US20100285397A1
Cited By
Charge adsorption material for cooperative treatment of multiple pollutants in fire area of coal field as well as preparation method and application of charge adsorption material
CN121372332A
